Pelaksanaan Workshop Literasi Keuangan dan Kesiapan Berumah Tangga di Desa Madiredo Kecamatan Pujon - Alif Achadah; Novita Fadia Rahma P; Faizatul Husnah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Financial literacy and family readiness are crucial aspects of building a community's economic and social well-being. Poor public understanding of family financial management, financial planning, and mental and social readiness in family life can trigger various economic problems and family conflict. This community service activity aims to improve the community's understanding of financial literacy and family readiness in Madiredo Village, Pujon District, through an educational workshop. The methods used in this activity were surveys and participant observation. Surveys were conducted before and after the workshop to measure participants' level of understanding regarding personal financial management, family financial planning, financial risk management, and readiness to build a harmonious household. Participatory observation was conducted throughout the workshop to determine participants' level of participation, enthusiasm, and interaction with the material presented by students from the Raden Rahmat Islamic University of Malang's Community Service Program (KKN-T). The results of the activity indicate an increase in community understanding of the importance of saving, prioritizing needs, managing family finances, and readiness to face the responsibilities of family life. This workshop is expected to be the first step in sustainably improving the quality of economic and social life in the village community